'Wo-manity' in the yoke of the harem: European women travel writers, authors and journalists of the 17th, 18th , 19th and early 20th centuries - Irene Kamberidou (Presentation at Media, Religion and Gender in Europe: RISECI –Religion in the Shaping of European Cultural Identity”, with the support of the Culture programme of the European Union, Barcelona Spain, 2014)
Presentation at “Media, Religion and Gender in Europe: RISECI –Religion in the Shaping of European Cultural Identity”, organized by the Blanquerna Faculty of Communication and International Relations, University Ramon Llull, with the support of the Culture programme of the European Union, Barcelona, June 13, 2014. ---------------------------------------------------------------ABSTRACT------------------------------   A cross-examination of the personal accounts of 210 women travelers and harem inmates of the 17th, 18th and 19th centuries in Asia Minor, Greece, Cyprus, Egypt, Africa and other occupied Ottoman territories “the real position of women in the religious system of Islam” (Garnett, 1895: 61). Women travelers from England, France, Germany, Switzerland, Sweden, Austria and America succeeded in doing what no male traveler, no man, had been able to do before or after them.  They surpassed the socio-religious barriers of Islam and penetrated into the gendered sphere and gendered boundaries of the Ottoman family/household, in other words the multiethnic harems of all the socioeconomic classes in Ottoman society. In contrast to their male counterparts, European and American women identify with the so-called  “Other”  using terms such as “Privileged Rape”, “Slavedom”, “Womanity”, “Woman-kind”, “Liberty”, “Freedom”, “Emancipation”, “Rape”, etc. They discuss the legal position and social privileges of free Muslim women and that of their islamized slaves, who were enslaved women and children of different nations. Namely, the female accounts focus on women’s legal rights with regard to marriage, divorce, child custody, inheritance, veiling or imposed covering of the Muslim female’s face and body, Ottoman sexual politics, among other things.----------------------------------------------------------------------------------------------------------------   MME, ΘΡΗΣΚΕΙΑ ΚΑΙ ΦΥΛΟ ΣΤΗΝ ΕΥΡΩΠΗ: Η ΘΡΗΣΚΕΙΑ ΣΤΗ ΔΙΑΜΟΡΦΩΣΗ ΤΗΣ ΠΟΛΙΤΙΣΤΙΚΗΣ ΤΑΥΤΟΤΗΤΑΣ **Irene Kamberidou (2014). "Wo-manity" in the yoke of the harem:  European women travel writers, authors and journalists of the 17th , 18th, 19th and early 20th centuries.   With Dr. Joseph M. Carbonell, Dean of the Blanquerna Faculty of Communication and International Relations, University Ramon Llull; Dr. Miriam Diez Bosch, Director of the Observatory on Media, Religion and Culture; Dr. Jordi Sanchez, Deputy Director of Blanquerna Observatory and other participants: Dr. Caroline Wilson, Duoda, Woen’s Research Centre, University of Barcelona Dr. Silvia Planas, Director of History of Jews Museum and Institute Nahmanides in Girona. Dr. Mia Lovheim, Professor of Sociology of Religion, Univerisy of Upsala Dr. Emiliana di Blasio, professor of sociology, Rome Dr. Gaspar Martinez, Professor of Votproa Tjeppgu Faculty Dr. Gloria Garcia Romeral Dr. Joanna Sumiala, Universioty of Helsinki Dr. Jordi Sanchez, Deputy Director of Blanquerna Observatory       Riseci.eu University Ramon Llull   Media, Religion and Gender in Europe/ MME, ΘΡΗΣΚΕΙΑ ΚΑΙ ΦΥΛΟ ΣΤΗΝ ΕΥΡΩΠΗ (Barcelona, June 13, 2014), RISECI –Religion in the Shaping of European Cultural Identity/ Η ΘΡΗΣΚΕΙΑ ΣΤΗ ΔΙΑΜΟΡΦΩΣΗ ΤΗΣ ΠΟΛΙΤΙΣΤΙΚΗΣ ΤΑΥΤΟΤΗΤΑΣ The Dean, Dr. Joseph M. Carbonell, Dean of the Blanquerna Faculty of Communication and International Relations, University Ramon Llull Dr. Miriam Diez Bosch, Director of the Observatory on Media, Religion and Culture Dr. Caroline Wilson, Duoda, Woen’s Research Centre, University of Barcelona Dr. Silvia Planas, Director of History of Jews Museum and Institute Nahmanides in Girona. Dr. Mia Lovheim, Professor of Sociology of Religion, Univerisy of Ups[psala Dr. Emiliana di Blasio, professor of sociology, Rome Dr. Gaspar Martinez, Professor of Votproa Tjep;pgu Faculty Dr. Gloria Garcia Romeral Dr. Joanna Sumiala, Universioty of Helsinki Dr. Jordi Sanchez, Deputy Director of Blanquerna Observatory     Barcelona June 14, 2014, after session on Media, Religion and Gender in Europe At the Picasso Museum https://www.facebook.com/obsblanquerna https://www.facebook.com/riseci http://www.periodistadigital.com/religion/opinion/2014/06/13/genero-religion-y-comunicacion-religion-iglesia-blanquerna.shtml